Promoting active and healthy living through cooperation: Involving stakeholders in innovative projects - Louceiro, Juliana; Dantas, Carina; Machado, Natália; Cabrita, Miriam; Saavedra, Ines (Magyar Gerontológia, 2024)
The ageing of the population in Europe implies rethinking several socio-economic issues and promoting the creation of opportunities that allow people to age well. To develop successful solutions, bringing together the different stakeholders to a shared discussion is crucial.